Determinants of the development of slow cities in Poland - Farelnik, Eliza (Uwarunkowania rozwoju slow cities w Polsce, 2019)
The aim of this study was to identify the factors, determinants and barriers in the development of slow cities in Poland, with special attention paid to those connected with specific features of the slow city model and membership in the Cittaslow network. The research subject was the factors and determinants of the development of member cities of the Polish National Cittaslow Network. All analyses and conclusions were mainly based on a critical examination of the literature. An identification of determinants and factors involved in the development of slow cities in Poland was made, including the division of them into local, regional, national, international and global categories. Attention was drawn to the determinants of implementing the slow city model connected with the contemporary paradigm of the development of cities, which should be considered in the management of slow cities in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 18-36
Keywords: Cittaslow; slow city; determinants of development; small cities; uwarunkowania rozwoju; małe miasta